INSTRUCTIONAL COMMUNICATION TEACHER OF CHILDREN FOUNDATION IN AUTISTIC CHILDREN INDEPENDENT PEKANBARU - Annisa Prishelly; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Autism is a developmental disorder that is indicated by symptoms such as lack of communication skills, social interaction, cognitive function, behavior and sensory abilities that require special handling by autism in special schools. This study aims to determine the instructional communication methods used in Pekanbaru Independent School Children Foundation, knowing the media used in the classroom, and barriers to what happens in the learning process.This study uses qualitative research methods to the presentation of the descriptive analysis. The subjects were teachers, parents, and students with autism in Pekanbaru while the Independent Children's Foundation is a research object to the teacher instructional communication of children with autism in the Independent Children's Foundation Pekanbaru. Data collection techniques used were observation, interviews, and documentation. In reaching the validity of the data in this study, researchers used an extension of participation and triangulation.The results obtained indicate that the instructional methods used by teachers of children with autism in school autism Independent Children's Foundation is programmed using an instructional method, simulation method, and the method of demonstration. Instructional media were introduced to children with autism in the form of academic media and media sensory integration. Instructional communication barriers between children with autism and teachers include technical barriers and psychological barriers.Keywords : Children, Autistic, Instructional Communication , Foundation